Pengaruh PhET Simulations terhadap literasi sains peserta didik kelas IV SDN 6 Mesuji Timur - farida juwita; Niken Yuni Astiti; Amrina Izzatika; Ulwan Syafruddin (Universitas Sebelas Maret, 2026)
The problem addressed in this study was the low level of scientific literacy skills among fourth-grade students at SD Negeri 6 Mesuji Timur. This study aimed describe and analyze the effect of using PhET Simulations on the improvement ofstudents’ scientific literacy in the IPAS subject. This study employed a quantitative research method with an experimental approach. A quasi-experimental method was used, applying a non-equivalent control group design. The research population consisted of 40 students. The sampling technique used was non-probability sampling, specifically saturated sampling, in which the entire population was used as the research sample. Data were collected through tests, observations, and documentation. Data analysis was conducted using a simple linear regression test, which showed that the calculated F value was greater than or equal to the table F value. The results of this study indicated that the use of PhET Simulations in the IPAS subject had a significant effect on improving the scientific literacy of fourth grade students at SD Negeri 6 Mesuji Timur